Viscoelastic Properties of Carbon Nanotube Reinforced Polyurethane Foams through Dynamic Mechanical Analysis - Ok, Oytun; Kucukkalfa, Eyuphan; Yildiz, Kaan; Cebeci, Hulya (American Institute of Aeronautics and Astronautics (AIAA), 2024)
Carbon nanotubes (CNTs) have recently emerged as a promising reinforcement for polyurethane (PU) foam, with potential applications in the aerospace industry. This study focuses on a comprehensive evaluation of the mechanical and viscoelastic properties of CNT-reinforced PU foam through compression tests and dynamic mechanical analyses (DMA). The investigation encompasses samples with 0.05 wt.%, 0.075 wt.%, and 0.1 wt.% CNT reinforcement, as well as a neat foam, all possessing a density of 100 kg/m(3). Notably, the compressive modulus values of CNT-reinforced foams exhibited an increase of 10-15% in comparison to the neat foam, while maintaining comparable compressive strength values. Furthermore, DMA assessment unveiled a significant enhancement in the storage modulus (E') and complex modulus values for CNT-reinforced foams, which were up to 50% higher than those of the neat foam. The most remarkable result was obtained with the 0.1 wt. % CNT reinforced foam yielding 43% greater storage modulus compared to the neat foam. These compelling results underscore the potential of CNT-reinforced PU foams as an effective core material for structural sandwich composite components within the aerospace industry. The present research contributes valuable insights into the development of advanced materials for aerospace applications and other demanding sectors.